Circles and Mistakes: Interview with Tim Ingold - Tim Ingold; Blanca Callén; Melisa Duque (Diseña, 2023)
Tim Ingold is a British anthropologist, Social Anthropology Professor at the University of Aberdeen, Fellow of the British Academy, and Fellow of the Royal Society of Edinburgh. He has explored the relationship between anthropology, architecture, art, and design; and through his work, has invited us to ‘think through making’ and ‘learn by doing’.